AAPM Task Group 241: A medical physicist's guide to MRI‐guided focused ultrasound body systems. Issue 9 (29th July 2021) - Payne, Allison; Chopra, Rajiv; Ellens, Nicholas; Chen, Lili; Ghanouni, Pejman; Sammet, Steffen; Diederich, Chris; ter Haar, Gail; Parker, Dennis; Moonen, Chrit; Stafford, Jason; Moros, Eduardo; et al.
Abstract: Magnetic resonance‐guided focused ultrasound (MRgFUS) is a completely non‐invasive technology that has been approved by FDA to treat several diseases. This report, prepared by the American Association of Physicist in Medicine (AAPM) Task Group 241, provides background on MRgFUS technology with a focus on clinical body MRgFUS systems. The report addresses the issues of interest to the medical physics community, specific to the body MRgFUS system configuration, and provides recommendations on how to successfully implement and maintain a clinical MRgFUS program. The following sections describe the key features of typical MRgFUS systems and clinical workflow and provide key points and best practices for the medical physicist. Commonly used terms, metrics and physics are defined and sources of uncertainty that affect MRgFUS procedures are described. Finally, safety and quality assurance procedures are explained, the recommended role of the medical physicist in MRgFUS procedures is described, and regulatory requirements for planning clinical trials are detailed. Although this report is limited in scope to clinical body MRgFUS systems that are approved or currently undergoing clinical trials in the United States, much of the material presented is also applicable to systems designed for other applications.